Accelerating SARS-CoV-2 genomic surveillance in a routine clinical setting with nanopore sequencing - Sergio Buenestado-Serrano; Marta Herranz; Álvaro Otero-Sobrino; Andrea Molero-Salinas; Cristina Rodríguez-Grande; Amadeo Sanz-Pérez; María José Durán Galván; Pilar Catalán; Roberto Alonso; Patricia Muñoz; Laura Pérez-Lago; Darío García de Viedma (Elsevier, 2024)
Background: SARS-CoV-2 genomic analysis has been key to the provision of valuable data to meet both epidemiological and clinical demands. High-throughput sequencing, generally Illumina-based, has been necessary to ensure the widest coverage in global variant tracking. However, a speedier response is needed for nosocomial outbreak analyses and rapid identification of patients infected by emerging VOCs. An alternative based on nanopore sequencing may be better suited to delivering a faster response when required; however, although there are several studies offering side-by-side comparisons of Illumina and nanopore sequencing, evaluations of the usefulness in the hospital routine of the faster availability of data provided by nanopore are still lacking. Results: We performed a prospective 10-week nanopore-based sequencing in MinION in a routine laboratory setting, including 83 specimens where a faster response time was necessary. The specimens analyzed corresponded to i) international travellers in which lineages were assigned to determine the proper management/special isolation of the patients; ii) nosocomial infections and health-care-worker infections, where SNP-based comparisons were required to rule in/out epidemiological relationships and tailor specific interventions iii) sentinel cases and breakthrough infections to timely report to the Public Health authorities. MinION-based sequencing was compared with the standard procedures, supported on Illumina sequencing; MinION accelerated the delivery of results (anticipating results 1-12 days) and reduced costs per sample by 28€ compared to Illumina, without reducing accuracy in SNP calling. Conclusions: Parallel integration of Illumina and nanopore sequencing strategies is a suitable solution to ensure both high-throughput and rapid response to cope with accelerating the surveillance demands of SARS-CoV-2 while also maintaining accuracy.